Benefits of AI-Based Application in Facilitating English Learning - Damayanti, Alvionita; Kurniawan, Roni; Shalli Anziila, Astrid; Rahmawati, Titik; Rafi; Fauzi, Iwan (Pusat Kajian Bahasa Daerah & Budaya, 2025)
This study investigates the role of Artificial Intelligence (AI) applications in enhancing vocabulary acquisition and receptive skills—specifically reading and listening—in English language learning. Focusing on three widely used platforms—Memrise, Cake, and Duolingo—a literature review of 21 peer-reviewed sources was conducted. Findings indicate that Memrise effectively supports vocabulary retention through spaced repetition and native speaker input, Cake addresses listening comprehension challenges via authentic, adaptive video materials, and Duolingo promotes vocabulary growth and reading fluency through gamified, personalized learning. Collectively, these AI tools foster learner autonomy, sustain motivation, and create flexible, engaging learning environments. The study underscores the importance of strategically integrating AI technologies into English as a Foreign Language (EFL) instruction to address diverse learner needs and improve learning outcomes.